(untitled) (Training and Practice : Journal of Educational Sciences, 2024)
Children’s artistic studies are most often based on a well-functioning team. At the heart of this are the children, who form a close unit with their teachers. However, parental support, encouragement and the cultural capital that provides children with values and experiences from an early age are not negligible factors. In this study, we investigated parents’ musical biographies, their current artistic activities and habits, and their impact on their children. Our results confirm that parental education and occupation are determinants of cultural capital. Gender differences in relation to artistic activities can be seen, and there is a clear link between the impact of artistic activities in childhood and current occupations of this type, which spill over into children’s activities.